Evaluation of Heat Decarbonization Strategies and Their Impact on the Irish Gas Network - Aruna Chandrasekar; Eoin Syron (Gases, 2021)
Decarbonization of the heating sector is essential to meet the ambitious goals of the Paris Climate Agreement for 2050. However, poorly insulated buildings and industrial processes with high and intermittent heating demand will still require traditional boilers that burn fuel to avoid excessive burden on electrical networks. Therefore, it is important to assess the impact of residential, commercial, and industrial heat decarbonization strategies on the distribution and transmission gas networks. Using building energy models in EnergyPlus, the progressive decarbonization of gas-fueled heating was investigated by increasing insulation in buildings and increasing the efficiency of gas boilers. Industrial heat decarbonization was evaluated through a progressive move to lower-carbon fuel sources using MATLAB. The results indicated a maximum decrease of 19.9% in natural gas utilization due to the buildings’ thermal retrofits. This, coupled with a move toward the electrification of heat, will reduce volumes of gas being transported through the distribution gas network. However, the decarbonization of the industrial heat demand with hydrogen could result in up to a 380% increase in volumetric flow rate through the transmission network. A comparison between the decarbonization of domestic heating through gas and electrical heating is also carried out. The results indicated that gas networks can continue to play an essential role in the decarbonized energy systems of the future.